eLearning in the Hungarian Home Defence Force – results and challenges - Vörös, Miklós (Acta Agraria Kaposváriensis, 2006)
Being part of NATO, specialists of the Hungarian Home Defence Force are required to possess complex, interdisciplinary knowledge. They are expected to prepare for meeting challenges such as, versatility in theoretical and practical aspects alike, creativity, permanent self-development, learning, taking advantages of ICT. Due to structural changes and rapid growth of ICT, system of ways, methodology and didactics of education is undergoing changes. The new paradigm of education assisted by ICT is efficiency, that is, the time and cost-factors of providing an individual with instantly marketable knowledge. The organisational framework of distant learning is emerging in ZMNDU. The findings of the surveys conducted among teachers and students strengthened the experience proving the growth of importance of the role of self study and of the modern information and communication tools and electronic learning materials.